OCULAR MANAGEMENT OF MUCOPOLYSACCHARIDOSIS (MPS) - A. Ahmed, Azzam; M. Ahmed, Muna (Medicinski časopis, 2024)
Background and objectives: Mucopolysaccharidoses (MPS) are a collection of rare ailments of storage lysosomes distinguished by the aggregation of glycosaminoglycans (GAGs) at distinct regions of the eye. Follow-up is necessary to enable the right direction for the subsequent therapy. The objective of this research is to define the clinical presentation and treatment modalities in MPS patients. Methods: A total of 16 children diagnosed with MPS were followed-up for 10 years. All cases in this study underwent cycloplegic refraction using 1% cyclopentolate (API) and streak retinoscope (Keeler). Results: The findings confirmed that all patients (100%) presented with corneal cloudiness, half of them (50%) were diagnosed as having glaucoma and just above a third of children (37.5%) suffer from retinopathy. Conclusion: Early detection and diagnosis are crucial to protect the visual function, and experience at different levels is required for reaching the correct diagnosis.